2006
DOI: 10.1002/dev.20120
|View full text |Cite
|
Sign up to set email alerts
|

Preferential reaching across regions of hemispace in adults and children

Abstract: The purpose of the current study was to examine hand selection during reaching in children utilizing a developmental version of the preferential reaching paradigm (Bryden, Pryde, & Roy, 2000). A cross-sectional sample of eighty right-handed participants (ranging in age from 3 to 20 years) were asked to reach to objects located in different regions of hemispace. Each participant was asked to carry out two different actions, varying in degree of complexity, on the objects while the experimenter observed, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
78
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 43 publications
(69 reference statements)
12
78
0
4
Order By: Relevance
“…According to this idea, asymmetry in transfer occurs because the two arm controllers are differentially proficient for controlling different features of movement (i.e., dominant arm for controlling movement trajectory, nondominant arm for specifying final limb posture; Sainburg and Kalakanis 2000;Bagesteiro and Sainburg 2003;Wang and Sainburg 2007b), and the motor control system determines the direction of information flow depending on the compatibility between task requirements and arm proficiency. Thus, when the left arm performs a visuomotor adaptation task in a left workspace location following initial training with the right arm in a right workspace location, for example, the motor control system allows the nondominant controller to access all of the available information obtained during the right arm training, as indicated by a transfer of direction information from the right to the left arm (Wang and Sainburg 2006b), probably because the left arm is performing the task in a workspace in which the control system considers using this arm as a more affordable solution, as compared with using the right arm (Bryden & Roy, 2006;Gabbard & Helbig, 2004;Gabbard & Rabb, 2000). Such access would not be allowed if the left arm was performing the task in a workspace location shared by both arms, as observed in our previous studies (Sainburg and Wang 2002;Wang and Sainburg 2007a), because the control system would perceive using the right arm as a more viable option for controlling this type of information (i.e., trajectory control) in the given task-space.…”
Section: Discussionmentioning
confidence: 99%
“…According to this idea, asymmetry in transfer occurs because the two arm controllers are differentially proficient for controlling different features of movement (i.e., dominant arm for controlling movement trajectory, nondominant arm for specifying final limb posture; Sainburg and Kalakanis 2000;Bagesteiro and Sainburg 2003;Wang and Sainburg 2007b), and the motor control system determines the direction of information flow depending on the compatibility between task requirements and arm proficiency. Thus, when the left arm performs a visuomotor adaptation task in a left workspace location following initial training with the right arm in a right workspace location, for example, the motor control system allows the nondominant controller to access all of the available information obtained during the right arm training, as indicated by a transfer of direction information from the right to the left arm (Wang and Sainburg 2006b), probably because the left arm is performing the task in a workspace in which the control system considers using this arm as a more affordable solution, as compared with using the right arm (Bryden & Roy, 2006;Gabbard & Helbig, 2004;Gabbard & Rabb, 2000). Such access would not be allowed if the left arm was performing the task in a workspace location shared by both arms, as observed in our previous studies (Sainburg and Wang 2002;Wang and Sainburg 2007a), because the control system would perceive using the right arm as a more viable option for controlling this type of information (i.e., trajectory control) in the given task-space.…”
Section: Discussionmentioning
confidence: 99%
“…By combining the results of studies on limb selection with results from studies on limb performance, one might conclude that the two factors are, in fact, related. For example, it has been shown repeatedly that right-handed subjects tend to reach the nondominant limb to targets on the left side of the workspace and the dominant limb to targets located on the right side (Bryden et al 2000;Bryden and Roy 2006;Gabbard and Helbig 2004;Gonzalez and Goodale 2009;Mamolo et al 2004Mamolo et al , 2006Peters 1995). In addition, studies of interlimb motor performance have shown that reaches to the ipsilateral workspace often show advantages in reaction time, peak velocity, duration, final position accuracy, and movement trajectory relative to contralateral reaches (Carey et al 1996;Carson et al 1992Carson et al , 1993Chua et al 1992;van Der Staak 1975;Elliott et al 1993;Fisk and Goodale 1985;Ingum and Bjorklund 1994;Prablanc et al 1979).…”
mentioning
confidence: 99%
“…Em concordância com estudos prévios em bebês (Morange & Bloch, 1996), crianças (Gabbard & Helbig, 2004;Hill & Khanen, 2009;Leconte & Fagard, 2006) e adultos (Bryden & Roy, 2006), as posições laterais do brinquedo induziram a realização de alcances ipsilaterais na maioria dos bebês. Resultados de um estudo recente indicaram que a escolha de uma das mãos para alcançar objetos localizados lateralmente é influenciada pela dominância motora e pela demanda da tarefa (Gabbard & Helbig, 2004).…”
Section: Discussionunclassified
“…Os resultados indicaram que alcances dos objetos localizados lateralmente foram sempre ipsilaterais, enquanto que objetos posicionados na linha média foram alcançados mais frequentemente com a mão esquerda (ver Rönnqvist & Domellöf, 2006, para mesma tendência). Uso mais frequente da mão esquerda tem sido observado também para alcançar objetos posicionados ipsilateralmente em estudos em crianças entre 5 e 8 anos de idade (Leconte & Fagard, 2006) e adultos (Bryden & Roy, 2006). Esses dados indicam que a disposição de objetos, com referência a coordenadas egocên-tricas, influi na escolha da mão usada no alcance.…”
unclassified